Multilevel Multi-Hop Technique for more than one Forward Node to increase the Stability of Wireless Body Sensor Networks - Choudhary, Nitu; Kumar, Deepak (International Journal of Computer Sciences and Engineering, 2025)
As wireless body area network is used to keep watch on patient body by deploying nodes on human body, in this work we propose a heterogeneous model to enhance the network lifetime by minimizing path loss, low power consumption, increase throughput and dividing the load through the nodes with more than one forwarder node in each round. The selection of the forwarder nodes is based on cost equation having minimum distance from the sink and maximum energy. Which helps in having high stability and contribute high packet delivering to the sink